Bancada didática de vibrações: fabricação de sistema de transmissão e análise vibracional - Schran, Ronilson (2019)
This paper presents the process of sizing and manufacturing pulleys and belts to be used in a vibration bench, in order to enable students of the Industrial Maintenance Technology course to have different practical classes. A 50 mm drive pulley and a set of three 80 mm, 110 mm and 140 mm driven pulleys were machined from cast aluminum with profile A V-channels. Three belts were used, one for each pair of wheels. pulleys, defined as A-29, A-31 and A-33. Vibration analyzes were performed with the aid of a Fluke 810 vibration tester using the 50 mm diameter drive pulley and the 110 mm driven pulley. Five analyzes were performed in different situations after assembly; after mechanical adjustments; after balancing; with deliberate unbalance with four sets screw nut; with deliberate unbalance with two sets screw nut. From the analysis, the results show that when mounting the pulleys on the vibration bench, it was not possible to obtain a diagnosis due to the high levels of vibrations that the bench showed, evidencing the need to make adjustments in rotating mechanical systems. With the adjustments, the vibration diagnosis showed four different faults and an overall vibration value of 1.78 g (RMS). The diagnoses made it clear that the dynamic balancing of rotating mechanical parts is of paramount importance for their safe and efficient operation. After balancing the overall vibration value was reduced to 1.35 g (RMS). The addition of mass in the counterbalance disc showed that excess mass compromises the vibration diagnosis. However, it was evidenced the possibility of studying the effects that unbalance can promote in the didactic bench. The failures shown show that damage can occur to rotating equipment when the mechanical elements used are not properly maintained.